Mixing Temperature Measurement of Swirl Cold Flow Exiting Cold Exit of Vortex Tube - Mohd Hazwan, Yusof; Katanoda, Hiroshi (EDP Sciences, 2016)

(untitled)
Cold flow of a vortex tube exiting the tube with a swirl flow movement produces a temperature distribution at the cold exit. In order to measure the mixing temperature of a swirl cold flow exiting cold exit of vortex tube, a simple mixing chamber is created using pipe and copper mesh. It is observed through this experiment that the temperature differences between inlet and cold flow increases when the cold fraction is decreased from 1.0. In addition, the temperature differences between inlet and cold flow increases when the inlet pressure is increased from 0.2 MPa to 0.5 MPa. The maximum value of cooling capacity in this research is obtained at inlet pressure of 0.5MPa and cold fraction of 0.4.